Coexistence of apoptosis, pyroptosis, and necroptosis pathways in Celiac Disease - Ruera, Carolina Naymé (2023)
Usually, the massive elimination of cells under steady-state conditions occurs by apoptosis, which is also acknowledged to explain the loss of enterocytes in the small intestine of celiac disease (CD) patients. However, little is known about the role of proinflammatory cell death pathways in CD. Here, we have used confocal microscopy, western blot, and RT-qPCR analysis to assess the presence of regulated cell death pathways in the duodenum of CD patients. We found an increased number of dead (TUNEL+) cells in the lamina propria of small intestine of CD patients, most of them are plasma cells (CD138+). Many dying cells expressed FAS and were in close contact with CD3+ T cells. Caspase-8 and caspase-3 expression was increased in CD, confirming the activation of apoptosis. In parallel, caspase-1, IL-1β, and GSDMD were increased in CD samples indicating the presence of inflammasome-dependent pyroptosis. Necroptosis was also present, as shown by the increase of RIPK3 and phosphorylate MLKL. Analysis of published databases confirmed that CD has an increased expression of regulated cell death -related genes. Together, these results reveal that CD is characterized by cell death of different kinds. In particular, the presence of proinflammatory cell death pathways may contribute to mucosal damage.